Applications of Non-invasive and Novel Methods of Low-Field Nuclear Magnetic Resonance and Magnetic Resonance Imaging in Aquatic Products - Wang, Xin-Yun; Xie, Jing; Chen, Xin-Jun (Frontiers in Nutrition, 2021)
Aquatic products is popular fish throughout the world due to their satisfying flavor characteristics, as well as rich animal nutrition which provides a high value of food therapy, while they are easily oxidized and spoiled. It is necessary to detect aquatic products through rapid and accurate technology. Low-field nuclear magnetic resonance (LF-NMR) and magnetic resonance imaging (MRI) have been widely used in the aquatic products industry due to their sensitivity, fast analysis, nondestructive and low cost. The applications of LF-NMR in the measurement of the aquatic product's quality and nutrients (water, fat and protein) were summarized in this paper. The applications of aquatic products have been shown to depend on deep processing, storage and authentication. This review discussed the application of MRI technology in the quality control of aquatic products. Therefore, it will guide the application of the aquatic products industry and aim to supply the reader with both the theory of the method, as well as the practical applications in scientific research and industrial applications in rapid and non-destructive technology.